Utilisation of Augmented Reality (AR) and Virtual Reality (VR) in Education: A Systematic Review - Anum, Adelina; Apriyanto, Sigit (CV. Tripe Konsultan, 2025)
This review systematically examined the effectiveness and challenges of utilising Augmented Reality (AR) and Virtual Reality (VR) technologies in the field of education over the past decade. As immersive technologies developed, AR and VR offered new approaches that were interactive, contextual, and constructivist in the teaching and learning process. This study employed a systematic review method based on the PRISMA protocol to analyse 60 scholarly articles published between 2015 and 2025, covering various educational levels, fields of study, and learning outcome indicators. The findings revealed that the application of AR and VR generally enhanced conceptual understanding, motivation, student engagement, and psychomotor skills, particularly within the contexts of science, engineering, medical education, and vocational training. Nevertheless, the implementation of these technologies still faced several obstacles, including infrastructure limitations, teacher preparedness, and potential psychological effects such as disorientation and cybersickness. The review also highlighted a growing trend of collaboration between educational institutions and technology industries in the development of AR/VR content, as well as the importance of policy support in expanding access to and the quality of immersive technology-based learning. Thus, AR and VR held significant potential as integral components in the transformation of future educational ecosystems, provided they were accompanied by appropriate pedagogical strategies and adequate readiness of supporting ecosystems.